Fighting Ability Influences Mate Value in Late Adolescent Men - Fernandez-Tapia, A (Elsevier Ltd, 2015)
Several studies have demonstrated the relationship between handgrip strength (HGS) and fighting ability in men, which is a relevant trait for intrasexual competition to increase the probability of obtaining a mate. However, few studies have determined a relationship between fighting ability and men s self-perceived capacity to find, attract and retain a mate. This capacity is a complex compound of several traits that evolutionary psychology has called mate value. In the present study, in a population of late adolescent men from Chile (. M±. SD. =. 16.94. ±.89. years), we explored the relationship between fighting ability, estimated by both HGS and a self-perceived fighting ability questionnaire, and mate value, assessed with a self-perceived mate value components questionnaire. The results show a strong influence of fighting ability on mate value. This influence affects the subscales of "views from the opposite sex", "sociality" and "relationship history". However, we did not find an effect on the subscales of "wealth", "parenting" or "fear to failure". The relationship between mate value and fighting ability indicates that fighting ability is a relevant component in understanding men s reproductive behaviour, including intrasexual competition and intersexual selection. This effect was observed in adolescents, who have less mating experience than adults. © 2015.